2022
DOI: 10.1007/s40620-022-01492-w
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence for steroidal mineralocorticoid receptor antagonists in patients with chronic kidney disease

Abstract: Background Mineralocorticoid receptor antagonists (MRAs) were shown to delay chronic kidney disease (CKD) progression in patients with hypertension and/or heart failure (HF) and proteinuria. Objective We conducted a systematic literature review on real-world evidence to identify the literature gaps related to the efficacy and safety outcomes of MRAs administered to CKD patients. Results A total of 751 records were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Data on the effect of steroidal MR antagonists in patients with CKD are limited [203]. A Cochrane review demonstrated that in patients with CKD, spironolactone reduced proteinuria and systolic/diastolic blood pressure [204].…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 99%
“…Data on the effect of steroidal MR antagonists in patients with CKD are limited [203]. A Cochrane review demonstrated that in patients with CKD, spironolactone reduced proteinuria and systolic/diastolic blood pressure [204].…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 99%